STUDY OF HEART TYPE FATTY ACID BINDING PROTEIN IN DIABETIC PATIENTS - Assist. Prof. Dr. Dr. Yildiz Hasan Tahseen (Web of Journals Publishing, 2024)
The majority of the cytoplasmic molecule the heart contains a protein called heart-type fatty acid-binding protein (H-FABP). After a myocardial infarction, it can be seen as early as 30 to 90 minutes in the blood. After peaking at 4 to 6 hours, it takes about 24 hours to recover to baseline levels. Because H-FABP is so sensitive early on in an acute MI episode, it has been recommended for usage in milder forms of subclinical myocyte injury as well as in the initial diagnosis of MI. Type 2 diabetes mellitus increases the risk of heart failure (T2D), based on an increasing amount of studies. Conclusion: H-FABP is a crucial predicator of HF in DM. Higher threat of perioperative cardiac death in diabetic patients associated with H-FABP. H-FABP intensities are higher in patients with HF who have a lower ejection fraction. An elevated plasma H-FABP may take a part in the etiology of chronic kidney diseases in diabetic patients. The review that is being given summarizes research on diabetes mellitus and H-FABP that was conducted in Iraq and a few other nations.
Keywords: H-FABP, Diabetes mellitus, heart failure, MI.